2021
DOI: 10.1016/j.exger.2021.111423
|View full text |Cite
|
Sign up to set email alerts
|

Do inflammaging and coagul-aging play a role as conditions contributing to the co-occurrence of the severe hyper-inflammatory state and deadly coagulopathy during COVID-19 in older people?

Abstract: The 2019 Coronavirus pneumonia (COVID-19) is a new infectious respiratory disease, which has caused a pandemic that has become the world's leading public health emergency, threatening people of all ages worldwide, especially the elderly. Complications of COVID-19 are closely related to an upregulation of the inflammatory response revealed by the pro-inflammatory profile of plasma cytokines (to the point of causing a cytokine storm), which is also a contributing cause of the associated coagulation disorders wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 120 publications
1
18
0
Order By: Relevance
“…In our study, the individual variance in the level of interleukin-6 (IL-6) was considerable among patients. A recent study found evidence to suggest that elderly patients were prone to a cytokine storm (Xu et al, 2021). Because of the high variance, there are conflicting findings on whether the age difference in IL-6 is notable (Zhao et al, 2020) or not (Peng et al, 2021).…”
Section: Dissimilarities In the Response To Covid-19 Among Age Groupsmentioning
confidence: 99%
“…In our study, the individual variance in the level of interleukin-6 (IL-6) was considerable among patients. A recent study found evidence to suggest that elderly patients were prone to a cytokine storm (Xu et al, 2021). Because of the high variance, there are conflicting findings on whether the age difference in IL-6 is notable (Zhao et al, 2020) or not (Peng et al, 2021).…”
Section: Dissimilarities In the Response To Covid-19 Among Age Groupsmentioning
confidence: 99%
“… Zambon et al 2018 [ 28 ] Research article Maternal obesity, periodontal disease and systemic and local inflammatory status during pregnancy. Pregnant Obesity, GDM and periodontal disease may synergistically amplify the inflammatory and oxidative status in pregnancy Xu et al 2021 [ 26 ] Review Inflammaging and severe hyper-inflammatory state during COVID-19 and other severe infections (sepsis). General Inflammaging and coagulating determine adverse course of viral and bacterial severe infections.…”
Section: Etiological Factorsmentioning
confidence: 99%
“…Several chronic comorbidities, including cardiovascular, metabolic, neoplastic, and autoimmune diseases, are strongly associated with inflammaging in a self-feeding vicious cycle where inflammaging may increase the risk of developing diseases and the disease itself exasperates the underlying age-related inflammation and immunosenescence. Inflammaging may also play a role in contributing to severe hyperinflammatory state and cytokine storm in case of superimposed infections, as in case of sepsis in elderly or SARS-CoV-2 infection [ 26 ].…”
Section: Etiological Factorsmentioning
confidence: 99%
“…Common causes of DIC in the elderly population include sepsis and cancer, especially acute myeloid leukemia (AML) [ 28 ]. However, research on the outcomes of DIC for the geriatric age group with these conditions are currently limited.…”
Section: Reviewmentioning
confidence: 99%